2016
DOI: 10.1038/srep30930
|View full text |Cite
|
Sign up to set email alerts
|

Extremely heat tolerant photo-symbiosis in a shallow marine benthic foraminifera

Abstract: Bleaching, the loss of algal symbionts, occurs in marine photosymbiotic organisms at water temperatures minimally exceeding average summer SST (sea surface temperatures). Pre-adaptation allows organisms to persist under warmer conditions, providing the tolerance can be carried to new habitats. Here we provide evidence for the existence of such adaptation in the benthic foraminifera Pararotalia calcariformata. This species occurs at a thermally polluted site in the Mediterranean, where water temperatures reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 41 publications
(76 reference statements)
0
29
0
Order By: Relevance
“…It is one of the few species that are constantly present within the warm station in Hadera, and its abundance is only reduced when temperatures exceed 33°C, while other species that are found within the heat‐polluted area are negatively affected already at 30°C (Arieli et al., ; Titelboim et al., ). Laboratory experiments confirmed that the photosymbiosis of the species remains functional up to 36°C (Schmidt et al., ) and that growth occurred between 20 and 35°C, inhibited in the range of 36–42°C, and significantly declined below 24°C (Schmidt et al., ). In this study, we documented calcification temperature of P. calcariformata as high as ~40°C, under natural conditions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is one of the few species that are constantly present within the warm station in Hadera, and its abundance is only reduced when temperatures exceed 33°C, while other species that are found within the heat‐polluted area are negatively affected already at 30°C (Arieli et al., ; Titelboim et al., ). Laboratory experiments confirmed that the photosymbiosis of the species remains functional up to 36°C (Schmidt et al., ) and that growth occurred between 20 and 35°C, inhibited in the range of 36–42°C, and significantly declined below 24°C (Schmidt et al., ). In this study, we documented calcification temperature of P. calcariformata as high as ~40°C, under natural conditions.…”
Section: Discussionmentioning
confidence: 89%
“…It recently invaded the eastern Mediterranean from the Red Sea and is now common from Israel to southern Turkey. It was recognized as heat tolerant relatively to other species in both field studies and laboratory experiments (Arieli et al., ; Schmidt et al., , ; Titelboim et al., ). Lachlanella sp.…”
Section: Introductionmentioning
confidence: 99%
“…During the cultivating period, the samples were kept under a daily cycle of 12 hours light / 12 hours dark using fluorescent light of ~30 µmol photons m -2 s -1 . These are lower than the photosynthetic optimum for A. lobifera (Ziegler and Uthicke, 2011), however, they were used to produce comparable data to that of related published papers (Schmidt et al, 2016b(Schmidt et al, , 2016a(Schmidt et al, , 2018Titelboim et al, 2019).…”
Section: Specimens Collection and Handlingmentioning
confidence: 99%
“…Next, we conducted another experiment on S. orbiculus in May 2019 to examine possible variation in thermal tolerance between winter and spring populations (following Schmidt et al, 2016a). The temperature manipulative experiments on A. lobifera were conducted only on the spring population that was sampled in May 2019.…”
Section: Laboratory Manipulative Experimentsmentioning
confidence: 99%
“…These heterotrophic mechanisms give them the ability to live in most marine sedimentary environments, from shallow‐water estuaries to deep‐sea basins. Some species developed further physiological adaptations, such as the capacity to store nitrate and to denitrify (Risgaard‐Petersen et al ., ; Piña‐Ochoa et al ., ; Bernhard et al ., ) and/or to host endo‐ and ectosymbionts (Bernhard et al ., ; ; ; ; Bernhard, ; Schmidt et al ., ). Among these adaptations, some species have the ability to ingest and maintain intact chloroplasts (kleptoplasts) in their cytosol from days to many months (Correia and Lee, ; Grzymski et al ., ).…”
Section: Introductionmentioning
confidence: 97%